2019
DOI: 10.1016/j.pld.2019.02.001
|View full text |Cite
|
Sign up to set email alerts
|

Comparative expression analysis of heavy metal ATPase subfamily genes between Cd-tolerant and Cd-sensitive turnip landraces

Abstract: The heavy metal ATPase (HMA) subfamily is mainly involved in heavy metal (HM) tolerance and transport in plants, but an understanding of the definite roles and mechanisms of most HMA members are still limited. In the present study, we identified 14 candidate HMA genes named BrrHMA1–BrrHMA8 from the turnip genome and analyzed the phylogeny, gene structure, chromosome distribution, and conserved domains and motifs of HMAs in turnip (Brassica rapa var. rapa). According to our phylogenetic tree, the BrrHMAs are di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 47 publications
(66 reference statements)
0
14
0
Order By: Relevance
“…Many efforts are underway to restrict exposure of humans to this metal by limiting the amount present in drinking water 2 and in the diet 3 . Crops that represent significant dietary sources of Cd include rice 2 , leafy [4][5][6] and other vegetables 7 , and also cacao (Theobroma cacao), the beans of which are the source of chocolate. The Cd contents of cacao beans show large regional variations, with the highest levels reported for material from South and Central America [8][9][10][11][12][13] .…”
Section: Introductionmentioning
confidence: 99%
“…Many efforts are underway to restrict exposure of humans to this metal by limiting the amount present in drinking water 2 and in the diet 3 . Crops that represent significant dietary sources of Cd include rice 2 , leafy [4][5][6] and other vegetables 7 , and also cacao (Theobroma cacao), the beans of which are the source of chocolate. The Cd contents of cacao beans show large regional variations, with the highest levels reported for material from South and Central America [8][9][10][11][12][13] .…”
Section: Introductionmentioning
confidence: 99%
“…Chaperone is an important way in delivering Cu to heavy metal P1B-ATPases [41]. In general, HMA contain approximately 6-8 transmembrane helices, a soluble nucleotide binding domain, phosphorylation domain, and a soluble actuator domain, of which HMA1-4 belonging to Zn 2+ /Co 2+ /Cd 2+ /Pb 2+ transporting, although HMA1 conserved amino acids is different from the HMA2, HMA3 and HMA4 [33], whereas HMA5-8 belong to the Cu + /Ag + subclass [51].…”
Section: Discussionmentioning
confidence: 99%
“…CtpB, as a plasma membrane copper (I) transporting P-type ATPase of Mycobacterium tuberculosis, is different from copper detoxi cation [77]. In [51].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…And cotton is an important fiber crop which provides the natural fiber for the textile industry [ 117 ]. Previously, much progress has been made in the identification of HMAD (heavy-metal-associated domain) genes in different plants [ 118 120 ]. However, there are no detail study has been reported in the identification, functional characterization, conserved domain analysis and expression profiles of the HMAD genes under salt-stress condition in cotton.…”
Section: Introductionmentioning
confidence: 99%